Strategi Manajemen Sumber Daya Manusia dalam Mendukung Kesehatan Mental Sandwich Generation pada Lingkungan Kerja - Ainunnisa, Khurotul; Nathalia, Nathalia; Jaya, Yadi Fakhruzein Terang (Universitas Harapan Bangsa, 2025)
This study analyzes effective Human Resource Management (HRM) strategies in supporting the mental health of the Sandwich Generation in the workplace. The sandwich generation is a middle-aged generation that has elderly parents and dependent children. This study uses a mixed method. The literature selection criteria include empirical research and concepts published in reputable national and international journals from 2015 to 2025 based on the relevance of the topics discussed, and interview data was obtained from employees who belong to the sandwich generation to strengthen the validity of the findings. The results show that the financial and emotional pressures experienced by the sandwich generation have a negative impact on productivity, emotional stability, and work well-being. Strategies that have proven effective include the provision of counseling services, mental support, social organization, stress management, and emotional education programs integrated with human resource management (HRM) policies. The implementation of these strategies is expected to improve employee mental well-being, strengthen loyalty, and improve organizational performance.